NILAI PEMBENTUK KARAKTER KEBANGSAAN PADA BUDAYA LOKAL KEE’RJA BANYAU - Fusnika Fusnika; Debora Korining Tyas (Universitas Negeri Malang, 2018)
This study aimed to provide an overview of the values that have been constructed the national character which found in the local culture of Kee’rja Banyau. The method used qualitative with a case study approach, data collected through observation, interviews, documentation. The findingsindicatethatlocalculturalvalues suchas Kee‘rja Banyau could beasource of maintaining the social integrity of a society which later became the forerunner of the embedded philosophy of life as part of the national identity. This is because in the local there are some national character values such as tolerance, friendliness or communicative, caring for the environment, social care and respon- sibility.